Analisis Dan Perancangan Sistem Pendukung Keputusan Seleksi Penerimaan Siswa Baru Dengan Metode SAW Dan WP Pada MAN 2 Kota Jambi - Anisa, Desfa; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2021)
Acceptance of new students in MAN 2 Jambi City is about 2 registration lanes namely the test path and the non test path. Reception of new students is always at school every year. However, the limitations of school facilities and infrastructure make it unable to accommodate all prospective students who have just registered, for this reason it is necessary to select the admission of new students. In this study, the authors approve computer-based decision support systems. This decision support system only supports limited assistance or provides recommendations in decisions not to support the decision maker's job. This new student selection decision support method was built using 2 methods, the SAW and WP methods. Then it is designed using case diagrams, activity diagrams and class diagrams.